Large Jejunoileal Duplication Cyst with Hyperplastic Polyps – A Case Report with Review of Literature - Ramyasree Bade; Jai Kumar Mahajan; Shailesh Solanki; Debajyoti Chatterjee (Indian Pediatrics Case Reports)
Background: Enteric duplication cysts (EDC) represent a rare developmental anomaly of the gastrointestinal tract, the most common site of origin being the ileum. Usually presenting within the early years of life, EDC may rarely have a delayed presentation. Clinical Description: A 4-year-old boy presented with chronic abdominal pain since the age of 2 years, along with poor weight gain and reduced oral intake. At 3 to 6 months of age, he had multiple episodes of melena which subsided without medical consultation. On examination, he was malnourished with pallor and normal systemic findings. Management and Outcome: Investigations revealed iron and vitamin B12 deficiency; stool and celiac work-up were negative. Ultrasound and computed tomography (CT) showed two hypoechoic lesions, one in the retroperitoneum behind the pancreas, and the other anterior to the superior mesenteric vein along with mural thickening in a segment of the bowel loop. Management was interrupted as the patient was lost to follow-up. On re-presentation at 7 years of age, due to persistent abdominal pain, a single-photon emission CT with 99m technetium pertechnetate study was consistent with multiple EDC with ectopic gastric mucosa. Endoscopy and biopsy further showed hyperplastic polyps within the duplication. Laparotomy and partial resection of the cyst and excision of the remaining segment with end-to-end jejunoileal anastomosis were done. Histopathology revealed >1000 sessile hyperplastic polyps without dysplasia. Postsurgery, the child recovered uneventfully and remained symptom-free at 1-year follow-up. Conclusion: Pediatricians need to be aware of the possibility of EDC with ectopic gastric mucosa in children with persistent abdominal pain and intermittent melena. This case is distinct due to the concurrent presence of hyperplastic epithelial polyps and the large length of the bowel involved. Early diagnosis and surgical correction can prevent childhood growth failure.